(3GdZjK GdYGQV aj oeYGQVI GHf GdaGQVs - (3CMeO Hf CHj MLdIs; (3GHf GdaGQV (B- (3SdWGf GdYGTbjf , YeQ Hf Ydj Hf eQTO Hf Ydj GdMehj, TQa GdOjf CHh MaU CHh GdbGSe,J (B632 (3g` s ((3GdTjN eMeO UGdM Gdfjfhj GdehUdj s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg adeG cGf OjhGf GHf GdaGQV ef CQb GdOhGhjf TYQkG hCfaSgG OQkG HMQkG hHQkG s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hCUMGHg hCRhGLg hPQjJg hCgd HjJg GdWjHjf GdWGgQjf hQVj Gddg Yf GdCQHYI GdeLJgOjf CLeYjf s
(3GdfSNI HgG MhGTs
(3OjhGf GHf GdaGQVs
(3cTa GdXfhf L (B1 (3U`(B767s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs